Temperature, violent crime, climate change, and vulnerability factors in 44 United States cities - Seulkee Heo; Hayon Michelle Choi; Jesse D. Berman; Michelle L. Bell (Environment International)
Biological and psychological theories suggest complex impacts of heat on aggression and violence. Most previous studies considered temporal intervals of months to years and assumed linear associations. Evidence is needed on daily impacts of temperature on crime, applying non-linear models across different locations. This observational study examined non-linear relationships between daily summer temperature (May–September) and violent crime in 44 cities across 33 US states, 2005–2022. We calculated city-specific average temperature for the event day and previous day (lag0–1) and daily temperature anomalies (deviation from 1985 to 2010 average) using PRISM data. The Uniform Crime Reporting Program data were used to calculate daily city-specific number of violent crimes (n = 2,447,458 incidents). Generalized additive modeling was used to estimate relative risks (RRs) of violent crime. We identified three distinctive shapes (J-shaped, inverted J-shaped, linear) for relationships. The inverted J-shaped curve, indicating higher crime rates at high temperatures below extremely hot temperatures, was most predominant (26 cities). Across all cities, violent crime was 1.03 times higher at high compared to moderate temperatures (90th vs. 50th percentiles) (RR 1.03, 95 % CI: 1.02–1.04). Violent crime was also higher at moderate compared to cold temperatures (50th vs. 10th percentiles) [RR 1.04 (95 % CI: 1.03–1.06)], whereas risk did not differ between extremely high and hot temperature (99th vs. 90th percentiles). Risk during hot days versus moderate temperature days was significantly lower for cities with lower latitude, higher median temperature, higher urban greenspace, and higher percentage of occupied housing units with air conditioners. Risk was higher in cities with 90th percentile temperature anomalies that deviated from the historical temperature record, suggesting implications of climate change on heat-related violence. High daily temperatures are associated with violent crime with differences across locations. Disparities in risks by city-level social and environmental characteristics have implications for climate change strategies.